Painted and Engraved Portrait in Russia in the Second Half of the 18th Century. The Problem of Correlation between an Image and a Word - Tetermazova, Zalina V. (Actual Problems of Theory and History of Art, 2013)
The article is dedicated to the problem of correlation between an Image and a Word in Russian portrait painting and engraving of the second half of the 18th c.
Keywords: engraving; painting; portrait; image and word; Russian art; 18th century